Social Capital and Family Planning Indicator in Indonesia: A Fixed Effect Analysis - Alifia Nugrahani Sidhi (Pusbindiklatren Bappenas, 2026)
Despite Indonesia’s family planning initiatives, modern contraceptive use has seen little progress over the past decade. This study investigates how women’s community participation, as a proxy for social capital, influences contraceptive behavior among women of reproductive age in rural and urban areas. Using panel data from the Indonesia Family Life Survey (IFLS) waves 4 and 5, fixed effects regression identifies the causal impact of community engagement. Results show that participation in health-related community groups increases the likelihood of modern contraceptive use by 11.5 percentage points compared to non-participation, while non-health-related activities have no significant effect. No rural–urban differences are observed. Decision-making autonomy and access to accurate contraceptive information strongly predict use, while education shows no consistent effect. These findings highlight the importance of health-related social capital in promoting contraceptive uptake. Policies should strengthen grassroots women’s health networks and integrate them more closely with national reproductive health programs. Keywords: community participation; Indonesia Family Life Survey (IFLS); modern contraceptive use; social capital.